Site‐Specific Gingival Bleeding on Probing in a Steady‐State Plaque Environment: Influence of Polymorphisms in the Interleukin‐1 Gene Cluster - Müller, Hans‐Peter; Barrieshi‐Nusair, Kefah M. (Journal of periodontology (1970), 2010)
Background: We previously reported a high prevalence of a combination of alleles 2 at positions interleukin (IL)‐1A−889 and IL‐1B+3954 in an Arabic population with gingivitis. In a steady state, the proportion of sites with bleeding on probing (BOP) was consistently reduced. The aim of the present study is to expand this observation by considering the site level. Methods: Fifty healthy non‐smoking volunteers, 19 to 28 years of age, participated in this study. Clinical examinations included probing depth, BOP, plaque index (PI), and calculus. Examinations were repeated after 2 and 4 weeks, and subjects were advised not to change oral hygiene habits. Polymorphisms in the IL‐1 gene cluster were assessed using a reverse hybridization assay. Results: Twenty‐six subjects (52%) carried alleles 2 at positions IL‐1A−889 and IL‐1B+3954 and were designated genotype positive. In multivariate multilevel models of BOP, bleeding tendency in subjects with positive IL‐1 genotype was only reduced at sites with PI 0 (odds ratio of 0.98, 0.65, and 0.56 at baseline and 2 and 4 weeks, respectively; χ2(3) = 11.946; P = 0.008) or 1 (χ2(3) = 6.027; P = 0.110). A decreased bleeding tendency at certain tooth types in subjects who were IL‐1 positive was largely related to the relative cleanliness of these areas. Random parts of the models revealed very low biserial correlations of 0.13 to 0.15 at the site level, whereas correlations were considerably higher (0.76 to 0.83) at the subject level. Conclusion: Multilevel modeling of site‐specific data yielded new information about the influence of the IL‐1 genotype in plaque‐induced gingivitis.